2015
DOI: 10.1890/es15-00206.1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of species phylogenetic relationships and species traits for the intensity of plant‐soil feedback

Abstract: Plant‐soil feedback (PSF) represents an important process affecting natural plant communities. While many previous studies demonstrated the variation in the intensity of PSF between species, the mechanisms driving these differences are still largely unexplored. The aim of the study was to explore the importance of species traits and species phylogenetic relationships on the intensity of plant‐soil feedback. To do this we used a classical design to test plant soil feedback, i.e., a two‐phase experiment consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 82 publications
2
32
0
Order By: Relevance
“…3A). Previous studies testing for this pattern showed contrasting results (Liu et al 2012, Mehrabi and Tuck 2015, M€ unzbergov a and Surinov a 2015, Fitzpatrick et al 2017). It is plausible that both increased pathogen sharing between close relatives, and increased mutualist sharing between distant relatives, causes a phylogenetic signal in plant-soil feedback.…”
Section: Stronger Negative Feedbacks In Soil Of Closely Related Plantmentioning
confidence: 89%
See 1 more Smart Citation
“…3A). Previous studies testing for this pattern showed contrasting results (Liu et al 2012, Mehrabi and Tuck 2015, M€ unzbergov a and Surinov a 2015, Fitzpatrick et al 2017). It is plausible that both increased pathogen sharing between close relatives, and increased mutualist sharing between distant relatives, causes a phylogenetic signal in plant-soil feedback.…”
Section: Stronger Negative Feedbacks In Soil Of Closely Related Plantmentioning
confidence: 89%
“…It is plausible that both increased pathogen sharing between close relatives, and increased mutualist sharing between distant relatives, causes a phylogenetic signal in plant-soil feedback. Previous studies testing for this pattern showed contrasting results (Liu et al 2012, Mehrabi and Tuck 2015, M€ unzbergov a and Surinov a 2015, Fitzpatrick et al 2017). Our approach of growing each plant on soils cultured by heterospecifics varying in phylogenetic distance to the target, may have more power to detect a phylogenetic signal in host range and studies on leaf pathogens and insect herbivores have used a similar approach to demonstrate phylogenetic signal in host range (Novotny andBasset 2005, Gilbert andWebb 2007).…”
Section: Stronger Negative Feedbacks In Soil Of Closely Related Plantmentioning
confidence: 89%
“…A lack of phylogenetic signal in δ 13 C could be indicative of differential trait combinations among species to achieve an overall carbon metabolism that is not necessarily phylogenetically conserved, despite conservatism in biochemical traits such as leaf nitrogen and Vc max . Leaf nitrogen has been reported to have phylogenetic signal for Magnoliaceae species (Liu et al, 2015) but not across the Ericaceae (Goud & Sparks, 2018) or closely related Asteraceae (Münzbergová & Šurinová, 2015). We previously used discrete foliar traits to characterize Asclepias habitat affiliations, with hairy & waxy species being from drier environments than glabrous species (Agrawal, Fishbein, Jetter, et al, 2009b).…”
Section: Variation In Ims: Leaf Traits Habitat Affiliations and Evmentioning
confidence: 99%
“…While studies have begun to uncover the variable role of evolutionary history in influencing PSF (Anacker et al 2014, Fitzpatrick et al 2017), a better understanding of the mechanisms underlying phylogenetic patterns in PSF is critical to advancing the field. Recent work suggests that evolutionary history can sometimes predict variable PSF (Liu et al 2012, Anacker et al 2014, M€ unzbergov a and Surinov a 2015, Kempel et al 2018, but there are also instances where it may not (Mehrabi and Tuck 2015, Fitzpatrick et al 2017. Such differences likely relate to varying degrees of phylogenetic trait conservatism (the tendency of lineages to retain traits through speciation events; Crisp and Cook 2012) in plant traits related to PSF.…”
Section: Introductionmentioning
confidence: 99%